Benefactions of Cultural Events Arts in Kenya Expanding Tourism Industry - Mugambi, Prof. Dennis (American Journal of Arts, Social and Humanity Studies, 2023)
Purpose: The purpose of this study is to determine the benefactions of the cultural festival on event tourism growth in Kenya. Methodology: The study a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: The study, in conclusion, found that there is a variety of cultural events arts held in Kenya. However, the cultural festivals, awareness strategies and their influence to tourism contributed to 21.0% to the growth of event tourism in Kenya. Unique Contribution to Theory, Practice and Policy: The study recommends that the Kenya Federal and State government together with stakeholder need to come up with policies and programmes to identify and promote cultural events arts as an event tourism product. The study found that marketing of cultural events arts was predominantly done locally as a strategy of creating awareness. The study, therefore, recommends that the Kenyan Tourism Corporation and Tourism Board market these rich cultural events arts internationally to reach the global customers